Investigation of a Worker Death While Agitating Manure in a Non-enclosed Storage. Issue 1 (2nd January 2018) - Shutske, John M.; Schaefer, Daniel; Larson, Rebecca; Erb, Kevin; Skjolaas, Cheryl; Leonard, Stephanie; Nelson, Jeff; Binversie, Elizabeth; Rifleman, Scott
ABSTRACT: An in-depth investigation of an unusual, non-enclosed manure storage hydrogen sulfide-induced fatality on a Holstein beef production operation is presented. The case involved several factors that likely played a role in the young farmer's death. These included zero wind movement, a reported temperature inversion in the area, relatively cool late summer outdoor temperatures on the morning of the incident, higher outdoor temperatures the week prior, and a high by-product steer ration containing ingredients that contributed significant sulfur content to the stored manure. Recommendations are offered for future research to determine the combinations of conditions and inputs that have potential to increase human and animal risk around manure storage structures. Based on this case and others recently documented showing unsafe levels of hydrogen sulfide being released from similar outdoor storages, it is critical that agricultural industry experts and input suppliers continue to analyze risk and consequences associated with new management practices, processes, inputs (including feed ingredients and animal bedding), machines, and other technology developed to support animal agriculture. Production practice and educational guidance are also offered based on this case and published literature.